Edukasi Kesehatan Reproduksi dan Skrining Kehamilan di Desa Kedungwungu, Kabupaten Banyuwangi: Studi Intervensi Komunitas - Permatasari, Ineke; Nita Indah Lestari; Rizky Dwiyanti Yunita; Tria Eni Rafika Devi (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2025)
The level of public awareness about reproductive health and the importance of pregnancy screening in rural areas is still low, resulting in a high risk of pregnancy complications. Kedungwungu Village, Banyuwangi, is one of the areas with suboptimal coverage of antenatal check-ups (K1). Education is provided with the aim of increasing community understanding of reproductive health and early detection of pregnancy risks through education and health screening. The service activities are carried out through: (1) Interactive counseling with visual media, (2) Individual counseling, (3) Basic health checks (blood pressure and physical examination). Participants consisted of 71 mothers who were purposively selected. After the activity, there was a 65% increase in participants' knowledge (from pretest to posttest) regarding reproductive health and pregnancy danger signs. Screening identified 1 mothers at risk of anemia who were get according to the procedure. Participants also showed high enthusiasm in group discussions. This program is effective in improving understanding and early detection of reproductive health problems. Continued collaboration with health cadres is needed to monitor at-risk participants.